Studi Morfologi Domba Ekor Gemuk Silangan (DEGS) Di Lembah Palu - Irfan, Mohamad; Dg. Malewa, Amiruddin (AgriSains, 2012)
This Research target to know the comparison form and size measure of parts of body (morfologi) of Fat Tail Sheep Livestock Traverse (female and Masculine DEGS) residing in Countryside of Bora and Chief Of Village Taipa Sulawesi Province. Parameter of livestock body qualitative and quantitative which Method used in this research is combination between "Frequency Relative" as which used by Mulliadi (1996) and Analyse The Especial Component (Principal Component Analyse) according to Gasperz (1992). Research result indicate that qualitative and quantitative sheep livestock in Countryside Bora more dominant form and also size measure of body compared to a sheep residing in Chief of village Taipa, this matter  strenghtened with the result analyse the especial component (AKU) (P>0,05) do not give the real influence among second of accurate sheep. that way also size measure parameter at female sheep like head footage, long  ear, long neck, long  body, long  back, long  thigh and tail length do not give the real influence (P>0,05). Key words : DEGS, morfologi.